menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Convert y - 1 = 2(x - 4) y + 2x = -7 x = -2y - 8 y = 2x - 7 y = 2x - 3 PLEASE ANSWER FAST LOL
asked
Dec 14, 2022
120k
views
4
votes
Convert y - 1 = 2(x - 4)
y + 2x = -7
x = -2y - 8
y = 2x - 7
y = 2x - 3
PLEASE ANSWER FAST LOL
Mathematics
middle-school
Pot
asked
by
Pot
4.7k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
2
votes
answer: y=2x-7
explanation:
y-1=2(x-4)
y−1=2x−2·4
y−1=2x−8
(y−1)+1=(2x−8)+1
y−1+1=2x−8+1
y=2x−7
Miroslav Nedyalkov
answered
Dec 17, 2022
by
Miroslav Nedyalkov
5.2k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
2
votes
The answer is y=2x-7
Jlconlin
answered
Dec 19, 2022
by
Jlconlin
4.9k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.3m
questions
6.9m
answers
Other Questions
Pizza planet is running a special 3 pizzas for 16.50. What is the unit rate for one pizza
What number is halfway between 0 and 18
how long Will it take for $7000 investment to grow to $7553 and the annual rate of 3.4% compounded quarterly assume that no withdrawals are made
I need to simplify this expression.
Need answer to math problem!!!
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org